IN VITRO CYTOTOXICITY AND ANTIOXIDANT EVALUATION OF BIOGENIC SYNTHESIZED GOLD NANOPARTICLES FROM MARSILEA QUADRIFOLIA ON LUNG AND OVARIAN CANCER CELLS - P., Balashanmugam; K., Mosa Christas; E., Kowsalya (International Journal of Applied Pharmaceutics, 2018)
Objective: The biogenic gold nanoparticles are considered to be extremely impressive for its wide range of applications in pharmaceutics and therapeutics. The present study was aimed at the biogenic synthesis of gold nanoparticles (AuNPs) from Marsilea quadrifolia aqueous extract and to investigate its antioxidant property and cytotoxic effect on human ovarian teratocarcinoma (PA-1) and lung adenocarcinoma (A549) cell lines. Methods: The biogenic AuNPs was synthesized using an aqueous extract of Marsilea quadrifolia. The synthesized biogenic AuNPs were characterized by ultraviolet (UV) visible spectroscopy, transmission electron microscopy (TEM), energy dispersive X-ray analysis (EDX) and X-ray diffraction (XRD). The biogenic AuNPs was assessed for its stability over a period of time and antioxidant activity. The cytotoxicity of biogenic AuNPs against PA-1 and A549 cell lines was studied using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Results: The synthesized biogenic AuNPs showed peculiar ruby red color and a surface plasmon resonance (SPR) peak at 544 nm in the UV-Vis spectrum. The characterization of biogenic AuNPs by TEM, EDX and XRD revealed well dispersed spherical particles ranging from 10-40 nm and the presence of elemental gold and its crystalline nature, respectively. The AuNPs showed good stability and the scavenging activity at 50 Î¼g/ml. The in vitro cytotoxicity of biogenic AuNPs against PA-1 and A549 cell lines recorded half maximal inhibitory concentration (IC50) of 45.88 Î¼g/ml and 52.015 Î¼g/ml, respectively. Conclusion: The biogenic AuNPs demonstrated superior antioxidant and antiproliferative activities against cancer cell lines.